Afferent and Efferent Visual Markers of Alzheimer’s Disease: A Review and Update in Early Stage Disease - Wu, Shirley Z.; Masurkar, Arjun V.; Balcer, Laura J. (Frontiers in Aging Neuroscience, 2020)
Vision, which requires extensive neural involvement, is often impaired in Alzheimer’s disease. Over the last few decades, accumulating evidence has shown that various visual functions and structures are compromised in Alzheimer’s dementia and when measured can detect those with dementia from those with normal aging. These visual changes involve both the afferent and efferent parts of the visual system, which correspond to the sensory and eye movement aspects of vision, respectively. There are fewer, but a growing number of studies, that focus on detection of predementia stages. Visual biomarkers that detect these stages are paramount in development of successful disease-modifying therapies by identifying appropriate research participants and in identifying those who would receive future therapies. This review provides a summary and update on common afferent and efferent visual markers of Alzheimer’s disease with a focus on mild cognitive impairment and preclinical disease detection. We further propose future directions in this area. Given the ease of performing visual tests, the accessibility of the eye, and advances in ocular technology, visual measures have the potential to be effective, practical, and non-invasive biomarkers of Alzheimer’s disease.